2000
DOI: 10.1002/1521-3765(20000616)6:12<2152::aid-chem2152>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation with a Non-Heme Iron Complex That Generates a Low-Spin FeIIIOOH Intermediate

Abstract: The antitumor drug bleomycin (BLM) is proposed to act via a low-spin iron(III) hydroperoxide intermediate called "activated bleomycin". To gain more insight into the mechanistic aspects of catalytic oxidation by these intermediates we have studied the reactivity of [(N4Py)Fe(CH3CN)](ClO4)2 (1) (N4Py = N,N-bis(2-pyridylmethyl)-N-bis(2-pyridyl)methylamine) with excess H2O2. Under these conditions a transient purple species is generated, [(N4Py)FeOOH]2- (2), which has spectroscopic features and reactivity strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 33 publications
(67 reference statements)
14
161
2
6
Order By: Relevance
“…Examination of the reactivity of 1b toward organic substrates has shown that this form is relatively inert compared to its conjugate acid. 38,71 A similar inertness has been noted for [Fe(EDTA)(η 2 -O 2 )] 3-. 39 A sideon peroxoiron(III) species has been postulated in the mechanism of arene cis-dihydroxylation by the Rieske dioxygenases 4, 74 and recently observed in the crystal structure of a ternary enzyme-substrate-O 2 complex of naphthalene dioxygenase.…”
Section: Summary and Perspectivesupporting
confidence: 70%
See 1 more Smart Citation
“…Examination of the reactivity of 1b toward organic substrates has shown that this form is relatively inert compared to its conjugate acid. 38,71 A similar inertness has been noted for [Fe(EDTA)(η 2 -O 2 )] 3-. 39 A sideon peroxoiron(III) species has been postulated in the mechanism of arene cis-dihydroxylation by the Rieske dioxygenases 4, 74 and recently observed in the crystal structure of a ternary enzyme-substrate-O 2 complex of naphthalene dioxygenase.…”
Section: Summary and Perspectivesupporting
confidence: 70%
“…In line with DFT calculations, [35][36][37] the low-spin iron(III) center plays a role in weakening the O-O bond and priming it for homolysis prior to substrate attack, a reactivity documented for 1a. 71 Comparison of 1a with activated bleomycin reveals major spectroscopic differences between the two complexes. First of all, the quadrupole splittings of both complexes (Table 2) differ substantially, and analysis of the g values with the Griffith model indicates that ∆/λ ≈ 12 for 1a compared to ∆/λ ≈ 8.74 20 for activated bleomycin.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…2, whereas more selective oxidants give substantially higher values. For example, values of 3.1-3.3 for [Fe(N4py)(CH 3 CN)](ClO 4 ) 2 were observed [15]. The relatively low C3/C2 ratio observed for catalyst 1 implies that the present catalytic reactions are distinct from a Fenton type free-radical oxidation reaction for which the typical C3/C2 ratios are higher than 20 [25].…”
Section: Resultsmentioning
confidence: 83%
“…Others include iron(II) complexes containing pyridine-based pentadentate ligands, with two to five pyridine rings [9][10][11][12][13][14][15][16]. These complexes can react with H 2 O 2 , forming metastable Fe-OOH intermediates, and in some cases to catalyze alkane hydroxylation [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…[84,101] The very high Fe IV/III redox potentials [123,124] suggest that the bispidine-based ferryl complexes should even be able to oxidise the strong C-H bonds of alkanes. [89,124] With bispidines and several other ligand systems, [125][126][127] various possible high-valent iron species were proposed to be responsible for substrate activation, i.e. Fe V ¼O (heterolytic O-O cleavage in the Fe III -OOH intermediate), Fe IV ¼O together with OH radicals (homolytic O-O cleavage in the Fe III precursor) or the products of direct oxidation of the Fe II precursor to the catalytically active Fe IV oxidant (see above).…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 99%